Generation of a squamous cell carcinoma mouse model for lineage tracing of BMI1+ cancer stem cells - Demeng Chen; Wuchang Zhang; Lingfei Jia; Cheng Wang; Cun-Yu Wang (STAR Protocols, 2021)
Summary: BMI1-expressing cancer stem cells (CSCs) play a key role in the development, progression, therapy resistance, recurrence, and metastasis of head and neck squamous cell carcinoma (HNSCC). Here, we present a chemically-induced HNSCC mouse model, genetically and pathologically similar to human HNSCC. This protocol describes how to use genetic lineage tracing based on the Cre-loxP recombination strategy, which allows us to study the regulation and targeting of BMI1+ CSCs in primary tumors and lymph node metastases.For complete details on the use and execution of this protocol, please refer to Chen et al. (2017) and Jia et al. (2020)